Badger game - Norris, William (Brentville, Tennessee CamCat Books, 2020)
The Mafia infiltrates a small Florida college to educate its members with a dubious curriculum. During the students$1 (Bsenior year, they join both major parties to help rig the election.s
Includes discussion questions and an excerpt from the author's title A Grave Too Many.
112533
Keywords: Mafia -- United States -- Fiction; Universities and colleges -- Florida -- Fiction; Presidents -- United States -- Election -- Fiction; Humorous fiction; Large print books